Strategi Humas Dinas Komunikasi dan Informatika Kabupaten Maluku Tenggara dalam Pengelolaan Informasi Publik - Kilmanun, Febyyola Welmina; Sopacua, Yustina (Jurnal Ilmu Komunikasi Pattimura, 2024)
The Department of Communication and Informatics (Diskominfo) of Southeast Maluku Regency plays a crucial role in supporting local governance and development. They focus on ensuring easy access to information for the public, especially in areas with limited internet coverage or low literacy rates. Diskominfo employs various strategies, including social media, digital platforms, as well as subscription-based radio and television stations. They are also responsible for providing public information services through various online platforms and seven public service applications. The information management process involves stages of collection, clarification, documentation, and distribution with principles of accurate news writing. Despite efforts to improve information access and public services, Diskominfo still faces several challenges such as telecommunication network blank spots, limited infrastructure, and the public's lack of knowledge about government information. To address these challenges, strategic issues such as expanding networks in blank spot areas, enhancing monitoring and evaluation, implementing electronic-based public service systems, and improving human resource capacity must be considered. Diskominfo of Southeast Maluku Regency continues to strive to ensure relevant and accurate information is available to the public, with the hope of supporting the development and empowerment of all layers of society in the region. Keywords: Strategies, Information Management System, Online, Diskominfo.